2008
DOI: 10.2478/v10045-008-0051-4
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Plant-Parasitic Nematodes Associated with Yams in Ogun and Osun States of Nigeria

Abstract: Abstract:A survey was conducted to determine the types, frequency and population of plant parasitic nematodes associated with the soils and roots of Yam (Dioscorea species) in all the Local Government Areas of Ogun and Osun States of Nigeria using random sampling soil and root and pie pan modification of Baerman funnel for plant parasitic nematode extraction. Ten and nine genera of plant parasitic nematodes were encountered both from the soils and root samples from the two States.Plant parasitic nematodes reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…A number of Dioscorea species are also the source of phyto-compounds which are used in the production of corticosteroids and have potential uses as excipients in the pharmaceutical industry (Poornima and Ravishankar 2007;Zuluaga et al 2007;Okunlola and Odeku 2011). Yam production has been constrained owing to several abiotic and biotic factors that include diseases and pests, inadequate planting material, low yield potential, and decreasing soil fertility (Amusa et al 2003;Adegbite et al 2006). Despite the vitality of yam, its genetic improvement through conventional breeding has been hindered by the prolonged breeding cycle, dioecious and erratic flowering nature, poor seed setting, polyploidy, vegetative propagation through seed tubers and vine cuttings, and heterozygous genetic background (Mignouna et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A number of Dioscorea species are also the source of phyto-compounds which are used in the production of corticosteroids and have potential uses as excipients in the pharmaceutical industry (Poornima and Ravishankar 2007;Zuluaga et al 2007;Okunlola and Odeku 2011). Yam production has been constrained owing to several abiotic and biotic factors that include diseases and pests, inadequate planting material, low yield potential, and decreasing soil fertility (Amusa et al 2003;Adegbite et al 2006). Despite the vitality of yam, its genetic improvement through conventional breeding has been hindered by the prolonged breeding cycle, dioecious and erratic flowering nature, poor seed setting, polyploidy, vegetative propagation through seed tubers and vine cuttings, and heterozygous genetic background (Mignouna et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the scores of S. bradys damage are observed with significant probability (P<0.001) ranging from 1 to 3 revealing significant difference between studied clones. (Adegbite et al 2006). This information can help to understand the tolerance of some clones of D. rotundata to both studied nematodes contrasting with data recorded for D. alata : They are probably more adapted to West Africa ecology constraints than D. alata .…”
Section: Climatic Growth Conditionsmentioning
confidence: 87%
“…R. reniformis is usually found in mixed populations with M. incognita and the disease symptoms in such situation is often only associated with root-knot nematodes. Many authors in Nigeria have found the reniform nematode in moderate populations associated with various crops (Adegbite et al, 2006;Olabiyi et al, 2009;Afolami et al, 2014;Daramola et al, 2015) but they did not consider the nematode to be damaging. This implies that the reniform nematode can be present in damaging populations and be left undiagnosed and uncontrolled due to lack of association as a potential pest problem.…”
Section: Discussionmentioning
confidence: 99%
“…Yield increases on okra, tomato, and lettuce of 19, 15, and 57% were obtained with treatment of granular nematicides, respectively on Rotylenchulus reniformis infested soil (Sikora and Fernandez, 2005). R. reniformis has been reported to be associated with various crops (Adegbite et al, 2006 ;Daramola and Afolami, 2014 ;Olabiyi et al, 2009) in Nigeria but has not been clearly connected to any quantitative loss of yield in Nigeria. The aim of this study was to assess the effect of the reniform and root-knot nematodes associated with the infection of okra.…”
Section: Introductionmentioning
confidence: 99%